Motivational variations in fitness: a population study of exercise modalities, gender and relationship status - Vuckovic, Vojko; Duric, Sasa (Frontiers in Psychology, 2024)
Motivation plays a crucial role in determining whether or not a person adheres to an exercise program. The present study aimed to determine the motivational differences between people exercising in fitness alone, in groups/aerobics and with a personal trainer by gender and relationship status. The EMI-2 questionnaire was completed by 830 users of 20 largest fitness centers in Slovenia. The Kruskal-Wallis test followed by a Dunn post-hoc test revealed that health-related motives such as ill-health avoidance were most frequently associated with exercising with a personal trainer compared to other exercise modalities, especially among females (p=0.032, M=4.88) and people in a relationship (p=0.020, M=5.18). On the other hand, intrinsic motivations such as enjoyment and stress management were mostly associated with exercising alone (p=0.002, M=4.98 and p=0.021, M=4.68, respectively). These results were also transferred to females and to some extent to people in a relationship (for enjoyment only). It is expected that intrinsic motivation is related to sustained exercise behavior. Future studies could implement a longitudinal design to test this statement and examine the proposed relationships over a longer period to better understand whether there may be causal relationships between motivation and different exercise modalities depending on different characteristics of participants.